2014
DOI: 10.1093/aje/kwu046
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Dichlorodiphenyltrichloroethane and Obesity at 9 Years of Age in the CHAMACOS Study Cohort

Abstract: In-utero exposure to endocrine-disrupting compounds, including dichlorodiphenyltrichloroethane (DDT) and its metabolite dichlorodiphenylethylene (DDE), has been hypothesized to increase the risk of obesity later in life. We examined the associations of maternal serum concentrations of DDT and DDE during pregnancy with body mass index, obesity, waist circumference, and percentage of body fat in 9-year-old children (n = 261) in the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
2
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 34 publications
3
80
2
7
Order By: Relevance
“…Similar to PCBs and TCDD, there appear to be different effects between genders, as some studies found associations with obesity in females but not in males(95) (101) (408). Conversely, two studies found effects on BMI, waist circumference, and overweight and obesity at 9 years (423) and weight at 14 years (127) in males but not in females. Additionally, an association between prenatal DDE and BMI z-score and rapid growth that was seen in both sexes was stronger in boys (265).…”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to PCBs and TCDD, there appear to be different effects between genders, as some studies found associations with obesity in females but not in males(95) (101) (408). Conversely, two studies found effects on BMI, waist circumference, and overweight and obesity at 9 years (423) and weight at 14 years (127) in males but not in females. Additionally, an association between prenatal DDE and BMI z-score and rapid growth that was seen in both sexes was stronger in boys (265).…”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 95%
“…Fifteen of 24 studies that investigated DDE exposures found positive associations between prenatal and early exposure to DDE and measures of obesity including BMI (189) (402) (414) (265) (189) (95) (423), weight (174) (189) (127), overweight (21, 408), rapid growth (265) (407), and waist circumference (383, 402) (101, 423). Only one 4-year study on Russian boys aged 6–8 years found a negative association between DDE and BMI (58).…”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
“…DDT can also be converted into biomethylsulfonyl metabolites, which are known to be potent toxic agents, particularly when reaching the adrenal gland. In addition, there is evidence to suggest that DDT plays an important role in the development of obesity [5,43,44]. DDT and its metabolites are thereafter eliminated mainly via urine and to a lesser extend in feces [45] as well as in breast milk [46].…”
Section: Toxicokinetics Of Main Pops and Their Metabolitesmentioning
confidence: 99%
“…Most research on prenatal and earlylife DDT exposure has focused on outcomes such as obesity, neurodevelopment, and breast cancer (37)(38)(39). However, shared mechanisms may provide links to RA; for example, endocrine disruption, inflammation, and stress response (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%